TEACHERS’ PROFESSIONAL SKILLS AS THE COMPONENT OF THE QUALITY OF HIGHER EDUCATION AND THE ELEMENT OF STUDENTS’ MOTIVATION - Chopyk, Roman; Hrybok, Nina; Zakalyak, Natalya; Lukjanchenko, Mykola (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The problem of studying the significance of teachers’ professional skills as the component of the quality of higher education and the element of students’ motivation is being analyzed in the article. The purpose of the research is study and analyzes of students’ attitude towards teachers’ professional skills as the component of the quality of higher education. The research has been conducted with the help of theoretical and empirical methods. Connection between the quality of higher education and teachers’ professional skills has been established with the help of dialectical method. The use of comparative method allowed us to implement the raking division of students’ attitude towards teachers’ professional skills. The empirical base of the research consists of the results of the survey of 175 students of Drohobych Ivan Franko State Pedagogical University. The following teachers’ professional skills: the ability to arouse the interest for the subject; clarity, accessibility and comprehensibility of the information layout; the ability to create a teamwork, motivate to achieve goals have been granted the highest ranking according to students’ attitude towards teachers’ professional skills. Such skills as objectivity and transparency of evaluation; goodwill and tactfulness; creative approach to studying; subject competence; erudition and culture of speech are highly evaluated. The following qualities: the culture of a dress code; organizational culture; the ability to act accordingly with moral, ethical and legal standards; the ability to recognize, formulate and solve problems constitute the interim position of the general ranking. Content significance and accessibility of the information which is being taught; skills of informational technologies; the ability to choose forms and methods of teaching which comply with student-oriented approach have been positioned at the lowest point of the general ranking according to the survey.